Spectrum of medial medullary infarction: clinical and magnetic resonance imaging findings - (:unkn) unknown (DR DIETRICH STEINKOPFF VERLAG, 2002)
Among 4200 consecutive patients admitted to three hospitals with acute ischemic stroke, we found only 11 patients in whom magnetic resonance imaging (MRI) had proved that they had medial medullary infarction (MMI). In our centers, patients with MMI were less than 1% of those with vertebrobasilar stroke. The infarcts documented by MRI were unilateral in 10 patients and bilateral in one. On clinico-topo-graphical analysis there were four clinical patterns: (1) Classical Dejerine's syndrome was the most frequent, consisting of contralateral hemiparesis, lemniscal sensory loss and ipsilateral lingual palsy in 7 of the eleven patients. (2) Pure hemiparesis was present in 2 patients; (3) Sensorimotor stroke was present in 1 patient with contralateral hemiparesis, hypesthesia and mild decrease in pain sensation without lingual palsy; (4) Bilateral MMI syndrome in I patient, accompanied by tetraparesis, bilateral loss of deep sensation, dysphagia, dysphonia and anarthria. Presumed causes of MMI were intrinsic branch penetrator artery disease with concomitant vertebral artery stenosis in 6 of the 11 patients, vertebral artery occlusion in 2, dolichoectatic vertebrobasilar arteries in 2, a source of cardiac embolism in 1. Prognosis at 3 months was favorable in 8 patients, but the patient with bilateral MMI syndrome had persisting motor deficit causing limitation of daily activities, and 2 died from systemic causes. The classical triad of acute MMI facilitates the diagnosis, although the recognition of this syndrome in patients with incomplete manifestations can be difficult and occurs more frequently than commonly thought. Moreover, vertebral artery atherosclerosis and branch atheromatous disease of the penetrating arteries are the main causes of medullary infarction.
Keywords: stroke; ischemia; medial medullary infarction; lingual palsy; PURE MOTOR HEMIPLEGIA; BRAIN-STEM; PYRAMIDAL INFARCTION; BILATERAL INFARCTION; UPBEAT NYSTAGMUS; STROKE; OBLONGATA; LESIONS; MRI